Identifying and managing incidents of minor theft within a service for individuals with intellectual disabilities - Smith, Martine (My University, 2019)
Background: Models of service delivery for adults with an intellectual disability in Ireland increasingly focus on delivering services within local communities. Preparation for this transition often focuses on practical skills. Our service received complaints about unacceptable behaviour (i.e., shoplifting), by some service users. Although such behaviours are relatively common in the general population, we found little research on this topic related to individuals with intellectual disabilities. Method: The Speech and Language Therapy Department surveyed families of individuals attending the service to explore the prevalence of concerns about such behaviours and any actions families had taken. Results: Over 34% of families who responded reported at least one incident of stealing. Such behaviours occurred within the home and in the community. Families had attempted a range of strategies to eliminate the behaviour, most often invoking a negative consequence. Conclusion: The combination of (a) changed opportunities arising from new service structures and (b) potentially reduced self‐control and/or immature self‐regulation, along with (c) inconsistent responses from the environment, forms a triad of influences that may contribute to the risk of stealing for some individuals with intellectual disability. Strategies adopted by the organisation to address this issue are outlined.
PUBLISHED
Keywords: community care; Family support; Health and social care policy and practice; Independent living; Intellectual disability; Community care; Inclusive Society; INTELLECTUAL DISABILITY; Intellectual Disability; Community; Communication; Home and community living; Social participation